2024
DOI: 10.1136/heartjnl-2023-323484
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of colchicine for the treatment of myopericarditis

Valentino Collini,
Maria De Martino,
Alessandro Andreis
et al.

Abstract: ObjectiveClinical trials have evaluated the efficacy and safety of colchicine only in simple pericarditis, excluding cases of concomitant myocarditis. The aim of this paper is to evaluate the efficacy and safety of colchicine for the treatment of the first attack of acute pericarditis with concomitant myocardial involvement.MethodsDouble-centre retrospective cohort study analysing consecutive patients admitted for first attack of pericarditis with myocarditis and treated with or without colchicine. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…At present, a retrospective study has demonstrated the safety and efficacy of colchicine on top of standard anti-inflammatory therapies in patients with myopericarditis. 4 …”
Section: Colchicine As First Successful Anti-inflammatory Drug For At...mentioning
confidence: 99%
“…At present, a retrospective study has demonstrated the safety and efficacy of colchicine on top of standard anti-inflammatory therapies in patients with myopericarditis. 4 …”
Section: Colchicine As First Successful Anti-inflammatory Drug For At...mentioning
confidence: 99%